(3fSeGJ GdSMQ hfaMGJ GdRgQs - (3eMeO Hf Ydj Hf eMeO GdShOj, CHh YHO Gddg eMjj GdOjf GdgGOj Gdjefj,J (B932 (3g` s
(3ChdgG (B:s
(3OdJfj Ydi GfbVGA gLQj Hjf SYOj aGQJMJ ef ScQj s
(3Vef eLehY s
(3hgh GdbSe GdKGfj ef OjhGf GdgGOj Gdjefj bWYI efg GNJdWJ ChQGbgG HeLehYI TYQjI CNQjIs
(3HHYV ChQGbgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B289 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B302 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B232s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B152 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1951s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs